1994
DOI: 10.2190/k892-pvlc-f1tt-tg1t
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Substance Use among Mexican American School-Age Children

Abstract: This article describes a study designed to examine the association of demographic, psychological, and environmental characteristics of a sample of low socioeconomic status, Mexican American students in elementary and middle school and their reported use of nine substances. Students in grades four, five, and six (N = 2295; males 52% and females 48%) located in a metropolitan school district in South Texas were surveyed in order to ascertain information pertaining to the initiation and/or ongoing use of substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Anglin et al 11,112 have described sex differences in initiation of heroin use and transition to dependence, yet this type of knowledge on sex differences in drug initiation is relatively sparse in comparison to our understanding of sex differences in later stages of drug involvement. The literature that has examined early opportunitites to try illicit drugs is sparse in itself [13][14][15][16] and has not attended to sex differences in early drug opportunities. By focusing on sex differences at the level of early opportunities to try illicit drugs, this study adds new evidence on sex differences in drug involvement.…”
Section: Introduction Tmentioning
confidence: 99%
“…Anglin et al 11,112 have described sex differences in initiation of heroin use and transition to dependence, yet this type of knowledge on sex differences in drug initiation is relatively sparse in comparison to our understanding of sex differences in later stages of drug involvement. The literature that has examined early opportunitites to try illicit drugs is sparse in itself [13][14][15][16] and has not attended to sex differences in early drug opportunities. By focusing on sex differences at the level of early opportunities to try illicit drugs, this study adds new evidence on sex differences in drug involvement.…”
Section: Introduction Tmentioning
confidence: 99%
“…Sensation seeking (Simon, Stacy, Sussman, & Dent, 1994), deviant behavior (Zapata & Katims, 1994), and increased unconventionality (Velez & Ungemack, 1995) were also associated with drug use among Latinos. Simon et al (1994) found that, among Latinos, high sensation seeking levels were significantly related to most substance use as well as the number of drugs used, but no such association was found for the non-Latino White students.…”
mentioning
confidence: 98%
“…For example, Amaro, Whitaker, Coffman, and Heeren (1990) found that marijuana and cocaine use was reported more often by U.S.-born Hispanics than by those who were born outside the continental US. However, others have found it to be associated with less drug use (Zapata & Katims, 1994). Confusion about the relationship between drug use and acculturation among Latinos may exist for several reasons, many of which have been discussed vis-à-vis their relationship to mental health (e.g., Rogler, Cortes, & Malgady, 1991).…”
mentioning
confidence: 99%
See 2 more Smart Citations